Exercise guidelines during pregnancy - Carnero, E. A.; Guilford, B. L.; Quesnel, D. A.; Cardona-Gonzalez, C.; Robert-McComb, J. J.; Fernandez-del-Valle, M. (The active female. Health issues throughout the lifespan, 2023)
The benefits of exercise during pregnancy (for both mother and fetus) are well-supported in the literature. As such, pregnant women have the opportunity to continue an exercise program throughout pregnancy without having to postpone activity engagement until after postpartum. Knowledge and consideration about the physiological adaptations of both pregnancy and exercise must serve as the cornerstone to guide exercise prescription. Understanding the health considerations prior to implementing an exercise program become particularly salient as the activity affects not only the female, but her unborn child as well. The following chapter will focus on understanding the physiological considerations required for prescribing exercise during pregnancy, in order to promote positive adaptations without increased risk of negative outcomes for the mother and fetus. This will be underlaid with a review of the main exercise prescription guidelines from the American College of Sports Medicine and the American College of Obstetricians and Gynecologists. Finally, practical ideas for exercises are suggested.